Recent Advances in the Herbal Treatment of Non-Alcoholic Fatty Liver Disease - Xiao, Jia (Medknow Publications & Media Pvt Ltd, 2013)
Non-alcoholic fatty liver disease (NAFLD) is one of the leading causes of chronic liver injury across the world. It is also strongly related to other pathological conditions, including obesity, diabetes, cardiovascular diseases, and symptoms of metabolic syndrome. Pathogenesis of NAFLD remains not fully characterized but is generally attributed to the occurrence of insulin resistance, lipid metabolism dysfunction,0 oxidative stress, inflammation, and necro-apoptosis. Every potential therapeutic strategy should target one or some of these pathological events in the liver. Over the past decades, application of herbal treatment for NAFLD has received increasing attention due to its wide availability, low side effects, and proven therapeutic mechanisms and benefits. In recent years, some monomers and certain functional mixtures of herbs have been extensively examined for their potential uses in NAFLD treatment. In the present review, we selected several herbal derivatives under intense basic and/or clinical investigations by carrying out a PubMed search of English language articles relevant to herbal derivatives and NAFLD, such as polysaccharide portion of wolfberry, garlic-derived monomers, red grape–derived resveratrol, and milk thistle–derived substances. They have been shown to target the pathological events during NAFLD initiation and progression both in pre-clinical studies and clinical trials. Although more detailed mechanistic researches and long-term clinical evaluations are needed for their future applications, they offer unanticipated and great health benefits without obvious adverse effects in NAFLD therapy.